Note on Pterygotus anglicus Agassiz (Eurypterida: Devonian) from the Campbellton Formation, New Brunswick - Miller, Randall (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1996)
Fragments of the large euryptcrid Pterygotus, recently collected from the Devonian Campbellton Formation at Atholville, New Brunswick, are identified as belonging to P. anglicus Agassiz. The only previous Pterygotus specimens from this site, collected in 1881, were assigned to a new species P. atlanticus Clarke and Rucdemann, in 1912. Clarke and Rucdcmann's suggestion that P. atlanticus might turn out to be a small specimen of P. anglicus is supported by this new find. However, possible revision of P. atlanticus awaits the discovery of additional, more complete, material.